There are 2 answers: choice B and choice F
==========================================
Step-by-step explanation:
Assuming the second "x+1" is all in the denominator, this will cancel with the first "x+1" in the numerator. I'm using the rule that x/x = 1 where x is nonzero.
What happens after the canceling is that f(x) = x-2. This is a linear equation with positive slope (the slope is 1).
The positive slope means the line goes up as we read it from left to right. As x gets larger, y does too. So we can say
![\text{ as } x \to \infty \text{ , } y \to \infty](https://img.qammunity.org/2020/formulas/mathematics/middle-school/a0d6tj0zam9pda506t7x7pmvogptmpbtr8.png)
Going in reverse, as x heads off to negative infinity, y does the same as well. Therefore,
![\text{as } x \to -\infty \text{ , } y \to -\infty](https://img.qammunity.org/2020/formulas/mathematics/middle-school/i7ka4rivbj36q1fr0tomwo6xheycbw0r91.png)
Below is the graph attached as an image to help visually verify the two answers. Note the hole at x = -1 which is due to the fact that this x value makes the original unsimplified version of f(x) to be undefined. Recall that we cannot divide by zero so x+1 cannot be equal to zero.